Cool eastern rim of the North Pacific during Late Cretaceous time: A seep-carbonate paleothermometry from the Nanaimo Group, British Columbia, Canada - Jenkins, Robert G.; Hasegawa, Takashi; Haggart, James W.; Goto, Akiko S.; Iwase, Yuya; Nakase, Chiharu (Palaeogeography, palaeoclimatology, palaeoecology, 2017)
A crater-shaped carbonate body newly recognized in the uppermost Northumberland Formation (Nanaimo Group) of the Canadian Pacific coast, is identified as a remnant of methane seepage during latest Campanian time in the northeastern Pacific region. A two meter-long elliptical mound with central concavity is found on a Cretaceous bedding plane observed at Hornby Island, British Columbia, exposed on an expansive intertidal platform. Microstructures characteristic of carbonate associated with methane seepage are readily observed within the rock body and indicate it was formed near the sediment-water interface. Carbon isotope values of the carbonate range between −45.5 and +4.9‰, where the lowermost values characterize anaerobic oxidation of biogenic methane as the primary process that controlled the carbonate precipitation. Oxygen isotope values also exhibit a wide range of values, from −9.8 to +0.6‰. Areas preserving features of earliest precipitation (i.e., radiaxial bladed calcite and micrite with clotted fabric) on cross-sections exhibit the highest δ18O values and indicate a paleotemperature 8.0±0.7°C for seawater at the seafloor. Development of cool water on uppermost bathyal or outer shelf depths in the northeastern North Pacific is thus implied during the Campanian-Maastrichtian transition. This paleotemperature determination shows a significant variance with those obtained from similar paleo-water depths of the northwestern North Pacific. [Display omitted] •A methane-derived carbonate mound was recognized from Late Cretaceous of North American Pacific.•The methane-derived carbonate from Nanaimo Group provides bottom water paleothermometry.•Latest Campanian cool (8.0±0.7°C) bottom seawater was identified at eastern rim of NE Pacific.•It offers opportunity to discuss paleoceanography of NE Pacific during CMBE cooling.